2022
DOI: 10.1155/2022/7792180
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Chitosan-Decorated Finasteride Solid Lipid Nanoparticles for Skin Drug Delivery

Abstract: Finasteride is considered the drug of choice for androgenic alopecia and benign prostate hyperplasia. The aim of the study was to formulate nanodrug carriers of finasteride with enhanced retentive properties in the skin. The finasteride was formulated as solid lipid nanoparticles that were decorated with different concentrations of chitosan for improved retentive properties. Solid lipid nanoparticles (SLNs) were synthesized by “high-speed homogenization technique” using stearic acid as a solid lipid while PEG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The presence of an additional PEG or chitosan layer provided the modified NLC formulations with additional steric stability, which reduced the coagulation of vesicles and eventually led to a reduction in growth rate [ 21 , 25 ]. Moreover, chitosan could increase repulsive forces among the positively charged surfaces of the NLC vesicles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an additional PEG or chitosan layer provided the modified NLC formulations with additional steric stability, which reduced the coagulation of vesicles and eventually led to a reduction in growth rate [ 21 , 25 ]. Moreover, chitosan could increase repulsive forces among the positively charged surfaces of the NLC vesicles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chitosan coating can improve the physical stability and extend the storage period of SLNs by over two times at 4 °C. Sohaib et al [ 129 ] confirmed that the drug-loading rate, drug release duration, and skin penetration were improved when finasteride, a lipophilic drug, was delivered to the skin through CS-SLNs in animal experiments.…”
Section: Surface Modifications Of Lipid Nanoparticlesmentioning
confidence: 99%
“…In the last two decades, UV-filter incorporation into lipid nanoparticles has been proposed as a promising strategy to develop formulations containing lower amounts of organic UV-filters without reducing the sun protection factor (SPF), due to the ability of these nanocarriers to act as physical sunscreens [15][16][17][18][19][20]. The first generation of lipid nanoparticles, namely solid lipid nanoparticles (SLN), consisted of a solid lipid core stabilized by surfactants in aqueous media [21][22][23][24][25][26][27][28]. Due to their drawbacks, such as poor stability and loading capacity, a second generation of lipid nanoparticles (nanostructured lipid carriers, NLC) whose core was made up of mixtures of liquid and solid lipids was developed [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%